Congenital Chagas disease: An update - Carlier, Yves (2015)
Congenital infection with Trypanosoma cruzi is a global problem, occurring on average in 5% of children born from chronically infected mothers in endemic areas, with variations depending on the region. This presentation aims to focus on and update epidemiological data, research methods, involved factors, control strategy and possible prevention of congenital infection with T. cruzi. Considering that etiological treatment of the child is always effective if performed before one year of age, the diagnosis of infection in pregnant women and their newborns has to become the standard of care and integrated into the surveillance programs of syphilis and human immunodeficiency virus. In addition to the standard tests, polymerase chain reaction performed on blood of neonates of infected mothers one month after birth might improve the diagnosis of congenital infection. Recent data bring out that its transmission can be prevented through treatment of infected women before they become pregnant. The role of parasite genotypes and host genetic factors in parasite transmission and development of infection in foetuses/neonates has to be more investigated in order to better estimate the risk factors and impact on health of congenital infection with T. cruzi.